Intestinal failure: a review - Allan, Philip (F1000Res, 2018)
Intestinal failure (IF) is the inability of the gut to absorb necessary water, macronutrients (carbohydrate, protein, and fat), micronutrients, and electrolytes sufficient to sustain life and requiring intravenous supplementation or replacement. Acute IF (types 1 and 2) is the initial phase of the illness and may last for weeks to a few months, and chronic IF (type 3) from months to years. The challenge of caring for patients with IF is not merely the management of the underlying condition leading to IF or the correct provision of appropriate nutrition or both but also the prevention of complications, whether thromboembolic phenomenon (for example, venous occlusion), central venous catheter-related bloodstream infection, IF-associated liver disease, or metabolic bone disease. This review looks at recent questions regarding chronic IF (type 3), its diagnosis and management, the role of the multidisciplinary team, and novel therapies, including hormonal treatment for short bowel syndrome but also surgical options for intestinal lengthening and intestinal transplant.